Socialization of Understanding of Financial Literacy and Financial Technology on the Financial Performance of Kebun Kelapa Village - Geby Citra Ananda; Annisa Ilmi Faried; Maya Syaula (Yayasan Multidimensi Kreatif, 2023)
This service aims to provide socialization and understanding of Financial Literacy and Technology in Kebun Kelapa Village. This training is carried out using practical and participatory methods, allowing participants to learn and implement the use of Android / mobile in the online complaint process. It is hoped that the results of this service in the future will make it easier for people to use Fintech products in Kebun Kelapa Village. By implementing this mobile-based online method, it will be easier for the community to improve the financial performance of their village. The positive impact of this training can be observed from the increase in people who are able to use online applications via their respective mobile phones. . Apart from that, this training also opens up new opportunities for village communities to utilize the potential of village communities with existing technological developments and effectively support sustainable village economic development. Through Financial Literacy and Financial Technology we can help village officials in matters.